Simultaneous treatment of phosphorus and fluoride wastewater using acid-modified iron-loaded electrode capacitive deionization: Preparation and performance - Dai, Zhijian; Qin, Tian; Bai, Chengke; Wu, Zhibin; Gao, Ya; Qin, Pufeng (Frontiers in Environmental Science, 2023)
Here, capacitive deionization technology (CDI) using modified activated carbon fiber felt (ACF) electrodes was proposed to provide a new strategy for the challenge of simultaneous phosphorus and fluoride wastewater treatment. The acid-modified iron-loaded ACF (A@Fe-ACF) was obtained by modifying ACF through a two-step impregnation method. After the modification, the oxygen-containing functional groups on ACF increased and provided more adsorption sites. The electron transfer efficiency on the A@Fe-ACF was increased by introducing Fe and synergistically promoted the adsorption of phosphorus and fluorine. Results showed that the removal efficiencies of total phosphorus (TP) and total fluorine (TF) in wastewater reached 89.4% and 85% under optimal conditions (voltage intensity 1.5 V, pH 7, plate spacing 1 cm), while the adsorption mechanism of phosphorus and fluorine was dominated by chemical adsorption. Meanwhile, A@Fe-ACF electrode has good recyclability and stability after 5 cycles.